Prostaglandin E1 vasospastic disease and thermography. Issue 2 (February 1985) - Kyle, V; Parr, G; Salisbury, R; Thomas, P P; Hazleman, B
Abstract : This is the first study to show a quantitative thermographic difference between patients with Raynaud's syndrome and normal controls after cold stress testing. An improved thermographic response to cold stress testing after treatment of Raynaud's syndrome with PGE1 has also been shown for the first time. Discriminant analysis of the change in temperature of a finger after cold stress, and the mean thermal gradient along the finger during rewarming, clearly separated patients from controls. After treatment with PGE1 the patients' discriminant values moved into the normal range. Symptomatic improvement after PGE1 correlated well with thermographic improvement, and both persisted for up to 12 weeks.